Chemical Characteristic of Frass Fertilizer Derived from Black Soldier Fly (BSF) Larvae Culture using Leftover Fruits and Vegetables - Mulyani, Sri; Mardiana, Mardiana; Fatmawati, Fatmawati; B, Muh. Fikruddin; Kafrawi Yunus, Muhammad (Devotion : Journal of Research and Community Service, 2025)
Toxic compounds such as chemical fertilizers have long been used in the agricultural and aquaculture sectors to improve soil fertility. Consequently, it adversely affects the soil, plants and aquaculture organism. Biodegradable waste can be converted into high-quality organic fertilizer. However, a proper candidate for treating biodegradable waste is required. A promising method for utilizing the black soldier fly (BSF, Hermetia illucens) larvae to derive the frass. The present study aims to determine the growth performance of maggots fed with leftover vegetables and fruit and its black soldier fly (BSF, Hermetia illucens) larvae frass chemical characteristic. The use of BSF larvae is to improve BSF frass fertilizer. A total of 3 experimental treatments were applied including; leftover vegetables (A), Fruit waste (B), Rice bran (C) as control treatment. Based on the results of the study, the type of food used as substrate affects the growth of larvae and the quality of the frass. In addition, there are differences in the length and weight of the larva produced by different types of food. This type of vegetable food provides the best maggot growth rate with an increase in length and weight. Several parameters of the chemical and biological properties of frass, the type of vegetable food suggest the highest N value.